أثر الإشراف الصحي على الأداء الوظيفي للعاملين: دراسة ميدانية بالمؤسسة الاستشفائية المتخصصة في رعاية الأمومة والطفولة بولاية برج بوعريريج - بلقرمى، سهام (جامعة عمار ثليجي بالأغواط - كلية العلوم الاجتماعية, 2018)
The study is concerned about exposing the effect of health supervision on job performance of employees in the hospital specialized in motherhood and childhood care of Bordj Bou Arreridj district. where upon, improving the level of performance and efficiency of all workgroups they are making or belong to; that evoked the attention to be aware about the role of health supervising to achieve that, adopting Fiedler's theory of effective leadership as a theoretical approach. The program (SPSS) was used to analyze the statistical data extracted from the components of the population study estimated in total of 95 medical and paramedical personnel including 49 people as a sample of physicians, midwives and nurses responsible for presenting health services. In general, the study attempted to answer the following problematic: What are the types of supervisory relationships within the hospital institution specializing in maternal and child care in Bordj Bou Arreridj city and how does this affect the professional performance of these workers?. The research concluded with a number of conclusions, the most important of which are: The consensus of the study sample on the positive role of health supervision in the maintenance of human relations in the health institution studied.
تهتم هذه الدراسة بإبراز أثر الإشراف الصحي على الأداء الوظيفي للعاملين في المؤسسة الاستشفائية المتخصصة في رعاية الأمومة والطفولة لولاية برج بوعريريج، حيث يعد موظفوها أساس نجاحها من خلال تحسين مستوى أدائهم وفعاليتهم، ومن ثمة تحسين مستوى أداء وفعالية فرق العمل التي يكونونها وينتمون إليها، ما استدعى الاهتمام بمعرفة دور الإشراف الصحي في تحقيق ذلك. وقد اعتمدت نظرية فيدلر المتعلقة بالقيادة الفعالة كمقاربة نظرية. واستعين ببرنامج الرزمة الإحصائية للعلوم الاجتماعية SPSS بهدف التحليل الإحصائي للبيانات المستخرجة من عناصر مجتمع الدراسة المقدر إجمالاً بـــــــــ 95 من الموظفين الطبيين وشبه الطبيين المكلفين بتقديم الخدمة الصحية من أطباء وقابلات وممرضين، فيما قدر حجم العينة بـ 49 فرداً. وبشكلٍ عام حاولت الدراسة الإجابة على التساؤل الآتي: ما نوع العلاقات الإشرافية بالمؤسسة الاستشفائية المتخصصة في رعاية الأمومة والطفولة بولاية برج بوعريريج وما مدى تأثيرها على الأداء الوظيفي للعاملين بها؟ وخلص البحث إلى مجموعة من الاستنتاجات أهمها إجماع أفراد عينة الدراسة على الدور الإيجابي للإشراف الصحي في الاهتمام بالعلاقات الإنسانية في المؤسسة الصحية المبحوثة.
Keywords: الإشراف الصحي -- الموارد البشرية -- الأداء الوظيفي -- المؤسسات الصحية